2019
DOI: 10.3390/nu11081724
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Science behind Bifidobacterium breve M-16V in Infant Health

Abstract: Probiotics intervention has been proposed as a feasible preventative approach against adverse health-related complications in infants. Nevertheless, the umbrella concept of probiotics has led to a massive application of probiotics in a range of products for promoting infant health, for which the strain-specificity, safety and efficacy findings associated with a specific probiotics strain are not clearly defined. Bifidobacterium breve M-16V is a commonly used probiotic strain in infants. M-16V has been demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 110 publications
(154 reference statements)
0
34
0
6
Order By: Relevance
“…The rationale behind the probiotic selection was established through pediatric use or following their source of origin linking with early life (i.e., isolation from infant feces or human milk). Moreover, some of them are actually included in infant formulas [50,57,58]. The dose was established in accordance with other studies [59,60].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The rationale behind the probiotic selection was established through pediatric use or following their source of origin linking with early life (i.e., isolation from infant feces or human milk). Moreover, some of them are actually included in infant formulas [50,57,58]. The dose was established in accordance with other studies [59,60].…”
Section: Discussionmentioning
confidence: 89%
“…Upon natural delivery, newborn rats were distributed into six groups of 24 animals each (three litters of eight animals/group): the reference (REF) group, the rotavirus-infected (RV) group, and four rotavirus-infected groups supplemented with: (1) Bifidobacterium breve M-16V, isolated from feces of a healthy infant [50]; (2) Lactobacillus acidophilus NCFM, isolated from adult human feces [51]; (3) Lactobacillus helveticus R0052, isolated from dairy culture [52]; and (4) Lactobacillus salivarius LMG P-27027 also referred to as Lactobacillus salivarius PS2, isolated from human milk [53]. All supplementations were provided by Danone Nutricia Research (Utrecht, The Netherlands).…”
Section: Experimental Designmentioning
confidence: 99%
“…The potential beneficial effects of Bifidobacterium breve M-16V strain on infant health (observed also in pre-term infants) have been recently presented in a review paper by Wong et al [84].…”
Section: The Impact Of Bifidobacterium Breve M-16v On Infant Immunitymentioning
confidence: 99%
“…In summary, we demonstrated that the administration of B. breve M-16V to mothers during pregnancy and breastfeeding prevented the development of OVA-induced asthma-like allergic inflammation accelerated by air pollution ROFA in their offspring by inhibiting Th2 immune responses and changes in their gut microbiota. Of note, B. breve M-16V is safe for use as a probiotic in humans including premature infants and pregnant women [23]. Thus, additional studies of the preventive potential of M-16V for allergic asthma are warranted, and M-16V might ultimately have clinical applicability.…”
Section: Plos Onementioning
confidence: 99%